Linguística histórica e Linguística de corpus - caminhos que se cruzam para desvelar a história da linguagem: um vocabulário bilíngue português-inglês - Yamamoto, Márcio Issamu (2015)
This dissertation addresses Historical Linguistics terminology, based on theoretical and methodological perspective of Corpus Linguistics (BERBER SARDINHA, 2004). It is also based on theoretical assumptions of the Communicative Theory of Terminology (CABRÉ, 1999), on the concept of Vocabulary (BARBOSA, 1990), the concept of Terminology (KRIEGER; FINATTO, 2004), and the defining contexts (AUBERT, 1996). The aims of this research are to: (I) build a bilingual terminological dictionary, English-Portuguese, comprising Brazilian and European Portuguese, which definitions, by contrast, will be elaborated from a Historical Linguistics terminological database whose users are translators and Language and Linguistics professionals and students; (II) build a Historical Linguistics domain tree (BARROS, 2004); (III) compile bilingual corpora; (IV) select the probable dictionary terms and, afterwards, seek for specialists confirmation; (V) make trustworthy data available for dictionary users; (VI) Organize data by using register tabs as dictionary entries; (VII) build up definitions for the selected terms; (VIII) make the outcome available at VoTec, a terminological management platform. For data analysis, WordSmith Tools 6.0 (SCOTT, 2012) is used. As a research outcome, it was observed that defining Historical Linguistics, as a linguistic domain itself, was quite a challenging task. Historical Linguistics is a domain that profits from other subdomains, especially as corpus, and from others to make its data analysis. Therefore, when it comes to Historical Linguistics, it comprises data from Etymology, Philology and Diachronic Linguistics. The Portuguese corpus comprises thesis, dissertations and academic articles, while the English one comprises conference proceedings, academic articles, thesis, anddissertations. Considering the terms for including in the dictionary, we have observed that corresponding terms are found in both corpora, and their definitions were written using proximate genus and specific difference patterns.